A formação humana integral: compreendendo a práxis do ensino e aprendizagem da biologia na Educação Profissional e Tecnológica de Nível Médio (EPTNM) - Aguiar, Aline Simões (Brasil, 2023)
The research emerged from the need to understand how praxis in the teaching of Biology can promote Integral Human Formation, in the perspective of a liberating education, capable of creating mechanisms in the classroom that allow the student to critically reflect on the social problems of the reality to be which is inserted. The research adhered to Line 01 of the Professional Master's Degree in Professional and Technological Education - Educational Practices in EPT, Macroproject 1 - Methodological proposals and didactic resources in formal and non-formal spaces of teaching in EPT. The methodological approach of the research followed the qualitative perspective of descriptive nature, based on participant research. The research locus was at the Federal Institute of Education, Science and Technology of Amazonas – IFAM/Campus Eirunepé. The research sample universe consisted of 10 (ten) students of the Technical Course of Medium Level in Agriculture in the Integrated form. It was applied as an instrument for data collection: two semi-structured questionnaires (pre-intervention and post intervention), and the elaboration of a workshop. After that, the interpretative analysis was carried out (SEVERINO, 2013), in the questions of a closed nature, and, for the open questions, the Content Analysis, by Bardin (2016). The study was based on the theories of Marx (2003), Marx and Engels (2002; 2007), Freire (2020), Ramos (2008; 2014), Silva (2020), among others. In general, the results indicated that it is not enough for the teacher to explain the content proposed in the Biology course syllabus, it is necessary to make an interlocution with questions that permeate the student's daily life, in the case of this research, the proposed themes were basic sanitation and the incidence of worms, in the perspective of a liberating education, promoting praxis. During the research, mainly in the data collection phase, several dialogues were established with the participants, which allowed an outline of the construction of the Educational Product (EP), entitled: The board game and the praxis for teaching Biology.